Growth performance study of Koi fish, Anabas testudineus (Bloch) by utilization of poultry viscera, as a potential fish feed ingredient, replacing fishmeal - Pratyush Bhaskar; Saroj Kumar Pyne; Arun Kumar Ray (International Journal of Recycling of Organic Waste in Agriculture)
Background In India, fishmeal is habitually considered as the major protein source for fish culture. Rising cost, deteriorating quality and unavailability of fishmeal caused huge difficulty in modern aquaculture, particularly for fish nutrition. Nearly all Anabas testudineus cultures faced loss, due to high feed costs, inappropriate feed formulation and management. So it was necessary to find a profitable replacement of fishmeal, which could provide better growth performance to A. testudineus. Results In this study, different types of poultry wastes were tested, and poultry viscera confirmed satisfactory results, having 60.67 % crude protein (% Dry matter basis). Further, a feeding trial was conducted for 60 days in 90-L circular fibre tanks with proper aeration, to evaluate poultry viscera, in the formulated diet for A. testudineus. Triplicate groups of fingerlings each were fed four isonitrogenous diets, at 5 % of wet body weight basis. Feed readjusted biweekly. Comparatively, fish accumulated highest and significant (P.05) increase in body weight and fat deposition, when dietary fishmeal completely replaced by poultry viscera. Discussions Thus, this study revealed that better growth performance in Koi, A. testudineus (Bloch) could be achieved through utilization of poultry viscera in the formulated fish feed, compared to fishmeal. Hence, poultry waste recycling could be stimulated also.